In Vitro Study to Evaluate the Thermal Changes on External Root Surface During the Use of Several Thermoplastic Filling Techniques (Journal of Hama University, 2019)
Recently, the usage of thermoplastic filling techniques has become very common in order to ensure the perfect fitting of gutta percha in the root canal. The Aim of this study is to evaluate the rise in temperature of the external surface of the root while using several thermoplastic filling techniques and the effect of dentine thickness on the rise in temperature .The sample include  60 mandibular one root premolars. The teeth lengths are  uniformed to 12mm after determining working length, and then shaped with Revo-s files #30. All roots were marked with two marks (the apex - and 5mm coronal to it) and temperatures are recorded using digital thermometer with probes. The sample is divided into 5 equal groups according to the obturation technique (thermoplastic obturation with EQ-V, thermoplastic obturation with HEROFILL, thermoplastic obturation with gutta condensor, vertical thermoplastic obturation and lateral condensation as control group). The temperature changes are recorded every 10 seconds at the two marks. The dentine thicknesses were measured at the coronal mark using CBCT. The results show that rising of roots’ external surface temperature is above the safe levels of 10 degrees in the middle third, without exceeding the safe duration of 1 minute and it is in opposite correlation with root dentine thicknesses. In conclusion, the heat-up duration of instrument used in continuous wave technique should not be too long. Also, we should be careful while using thermoplastic filling techniques in teeth with thin dentine walls.